Is a team different from the sum of its parts? Evidence from mutual fund managers - Michaela Bär; Alexander Kempf; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2005)
This paper provides the first empirical test of the diversification of opinions theory and the group shift theory using real business data. Our data set covers management teams and single managers of US equity mutual funds. Our results reject the group shift theory and support the diversification of opinions theory: extreme opinions of single team managers average out and, consequently, teams make less extreme decisions than individuals do. We find that teams follow less extreme investment styles and their portfolios are less industry concentrated than those of single managers and that teams are eventually less likely to achieve extreme performance outcomes. These results hold after taking into account the impact of fund and family characteristics as well as manager characteristics. Additionally, teams exhibit a lower active share and lower risk levels, driven by a lower level of idiosyncratic risk, as compared to singlemanaged funds.
Keywords: G23; M54; 330; Mutual Funds; Team Management; Investment Behavior